A flexible mid-term frequency domain scheduler for resource allocation in HetNets based on the SINR requested by users (2015)
This article treats the resource allocation problem for the downlink of a multi-cell, multiservice Wireless Mobile Communications System (WMCS) with heterogeneous architecture deployed into an urban environment using Long Term Evolution (LTE) and Orthogonal Frequency Division Multiple Access (OFDMA) in its physical level. The optimization model aims to satisfy services to users by making an efficient use of the available resources, and a fair frequency block allocation, using the Signal to Interference-plus-Noise Ratio (SINR). It is a Mixed Integer Nonlinear Programming (MINLP) model whose solution is complex to obtain directly. The proposed solution algorithm decouples the solution space of the problem and uses an iterative and semi-distributed approach to implement a frequency-domain scheduler in the medium term that uses a global vision of the system to allocate resources trying to obtain the SINR required for all users (the proposed goal). Since it is not always possible to achieve it, we take advantage of the elasticity of some of the services offered and incorporate a slack variable to solve it. The approach allows selecting the frequency allocation strategy, the exploration focus of the search space and the system administrator's vision. The results obtained show that the implementation that uses a coordinated frequency allocation obtains better results in the amount of users with full satisfaction and in the use of power when compared to implementations using other frequency allocation strategies. In scenarios with heterogeneous architecture, the combined effect of picocells and coordinated frequency allocation improves the value for the defined performance metrics.